LHCA4 residues surrounding red chlorophylls allow for fine-tuning of the spectral region for photosynthesis in Arabidopsis thaliana - Li, Xiuxiu; Zhu, Lixia; Song, Jince; Wang, Wenda; Kuang, Tingyun; Yang, Gongxian; Hao, Chenyang; Qin, Xiaochun (Frontiers in Plant Science, 2023)
Improving far-red light utilization could be an approach to increasing crop production under suboptimal conditions. In land plants, only a small part of far-red light can be used for photosynthesis, which is captured by the antenna proteins LHCAs of photosystem I (PSI) through the chlorophyll (Chl) pair a603 and a609. However, it is unknown how the energy level of Chls a603–a609 is fine-tuned by the local protein environment in vivo. In this study, we investigated how changing the amino acid ligand for Chl a603 in LHCA4, the most red-shifted LHCA in Arabidopsis thaliana, or one amino acid near Chl a609, affected the energy level of the resulting PSI-LHCI complexes in situ and in vitro. Substitutions of the Chl a603 ligand N99 caused a blue shift in fluorescence emission, whereas the E146Q substitution near Chl a609 expanded the emission range to the red. Purified PSI-LHCI complexes with N99 substitutions exhibited the same fluorescence emission maxima as their respective transgenic lines, while the extent of red shift in purified PSI-LHCI with the E146Q substitution was weaker than in the corresponding transgenic lines. We propose that substituting amino acids surrounding red Chls can tune their energy level higher or lower in vivo, while shifting the absorption spectrum more to the red could prove more difficult than shifting to the blue end of the spectrum. Here, we report the first in vivo exploration of changing the local protein environment on the energy level of the red Chls, providing new clues for engineering red/blue-shifted crops.